Development of Simvastatin Production by Monascus Purpureus In Solid-State Fermentation Using Agricultural Product - Farhan, Mohd Said (Malaysian Technical Universities Network (MTUN), 2015)
Monascuspurpureus is a non-pathogenic fungus that can produce statin called simvastatin, which can lower blood cholesterol level. The objectives of this research were to explore the potential of agricultural product on simvastatin and identify the optimal condition of simvastatin production in solid-state fermentation by Monascuspurpureus FTC 5356. The local agricultural products used were banana, guava, pumpkin, coconut meat, corn and papaya. Initially, the local agricultural products were ground and the initial moisture content of the agricultural products was fixed at 50% and pH 6. The mixtures were then incubated at 30°C for 11 days. Later, variety conditions of initial moisture content and nitrogen supplementation were introduced and examined on the simvastatin. Further experimental work was carried out using Central Composite Design (CCD) of Response Surface Methodology (RSM), with two factors of initial moisture content and nitrogen source. The results suggested that, among the agricultural products tested; only corn powder was able to produce simvastatin. The optimal condition for simvastatin production on corn was at 50% initial moisture content with supplementation of 0.2% nitrogen source.